A Nonlinear PIC Algorithm for High Frequency Waves in Magnetized Plasmas Based on Gyrocenter Gauge Kinetic Theory (Communications in Computational Physics, 2020)
Numerical methods based on gyrocenter gauge kinetic theory are suitablefor first principle simulations of high frequency waves in magnetized plasmas. Theδf gyrocenter gauge PIC simulation for linear rf wave has been previously realized.In this paper we further develop a full-f nonlinear PIC algorithm appropriate for thenonlinear physics of high frequency waves in magnetized plasmas. Numerical casesof linear rf waves are calculated as a benchmark for the nonlinear GyroGauge code,meanwhile, nonlinear rf-wave phenomena are studied. The technique and advantageof the reduction of the numerical noise in this full-f gyrocenter gauge PIC algorithmare also discussed.